Adipose tissue insulin resistance in adolescents with and without type 2 diabetes. Issue 5 (17th July 2013) - Kelsey, M. M.; Forster, J. E.; Van Pelt, R. E.; Reusch, J. E. B.; Nadeau, K. J.
Summary What is already known about this subject Type 2 diabetes is increasing in youth, but little is known about the underlying pathophysiology. Elevated fasting free fatty acids and failure of insulin to suppress lipolysis are well described in adults. Small studies suggest that obese youth with and without type 2 diabetes have impaired suppression of lipolysis, but there are little data on associated factors. What this study adds Assessment of insulin suppression of lipolysis in a larger cohort of adolescents using hyperinsulinaemic euglycaemic clamp technique at higher insulin doses than have been previously reported. Novel finding that some obese youth with and without type 2 diabetes have impaired suppression of lipolysis even at very high doses of insulin. Factors associated with impaired insulin suppression of lipolysis include high triglycerides, high alanine aminotransferase and high low‐density lipoprotein cholesterol. Background The incidence of type 2 diabetes mellitus (T2D) is increasing in youth, yet little is known about the underlying pathophysiology. Decreased insulin suppression of lipolysis and elevated non‐esterified free fatty acid (NEFA) concentrations are known to be associated with insulin resistance and T2D in adults, but less is known about the relationship in adolescents. Objectives This study aimed to assess adipose tissue insulin resistance (IR; insulin suppression of lipolysis) and its metabolic correlates in lean, obese and T2D adolescents. Methods Forty‐seven lean, obese and T2D youth underwent hyperinsulinaemic (80 mU*m−2*min−1) euglycaemic clamps. NEFAs were measured at baseline and during steady state. Insulin‐mediated suppression of lipolysis (%NEFA suppression from baseline) was calculated, and metabolic risk factors were assessed by %NEFA suppression tertile. Results There was expected variability in %NEFA suppression within obese and T2D youth, but a subset had significantly reduced suppression of lipolysis. NEFA suppression tertile was significantly inversely associated with fasting triglycerides (P = 0.0001), log alanine aminotransferase (ALT; P = 0.02) and low‐density lipoprotein cholesterol (P = 0.0002). Conclusions Marked adipose tissue IR occurs in some obese and T2D adolescents, which may result in release of triglycerides into the circulation and liver deposition of fatty acids, as evidenced by higher ALT in poor NEFA suppressors.